Going forward from B to A? Proposals for the Eurozone crisis - Massimo Amato; Luca Fantacci; Dimitri B. Papadimitriou; Gennaro Zezza (Economies, 2016)
After reviewing the main determinants of the current Eurozone crisis, this paper discusses the feasibility of introducing fiscal currencies as a way to restore fiscal space in peripheral countries, such as Greece, which have so far adopted austerity measures in order to abide by their commitments with Eurozone institutions and the IMF. We show that the introduction of fiscal currencies would speed up the recovery, without violating the rules of Eurozone Treaties. At the same time, these processes could help the transition of the euro from its current status of single currency to a status of 'common clearing currency' along the lines proposed by Keynes at Bretton Woods as a system of international settlements. Eurozone countries could therefore move from 'Plan B' aimed at addressing member state domestic problems, to a 'Plan A' of a better European monetary system.
Keywords: E02; E12; E42; F45; 330; euro; fiscal currencies; austerity; current account imbalances; Clearing Union